EKSISTENSI GURU SEKOLAH MINGGU DALAM MENINGKATKAN DIGITAL QUOTIENT KEPADA ANAK - Agus Mawarni Harefa (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
The development of human life today has been significantly influenced by the rapid advancement of technology. Behind the convenience and advancement of technology, it is not uncommon to have an unfavorable impact on its users. Nowadays, not a few children and teenagers are trapped in gadget abuse, for example; visiting pornographic sites and forgetting time to study because of addiction to online games. These events often result in the degradation of the child's character and spirituality. In addition, other factors that make children less controlled in using gadgets are due to the presence of some parents who do not provide guidance to children regarding the use of gadgets properly and regularly. The purpose of this writing is to explain the existence of Sunday school teachers in providing guidance and direction to increase Sunday school children's understanding of the use of gadgets by providing parenting guidance, teaching slowly the benefits of gadgets, utilizing the parental control features available on gadgets and determining sanctions for children if they violate the boundaries that have been given. The method used in writing this article is a qualitative method and a literature research approach. The results received in this study are that the more existence of Sunday school teachers in increasing the digital quotient for children, the more responsible Sunday school children will be for the gadgets they have.